Development of Burnup Fraction Calibration Curve for the Silicide Fuel Equilibrium Core of the RSG-GAS Reactor - Pinem, S.; Sulistyo, F. Y.; Liem, P. H.; Hakim, A. A.; Luthfi, W. (National Research and Innovation Agency, 2026)
The reactivity value of the RSG-GAS research reactor fuel with different burnup levels has been measured. The primary objective of this study is to establish the burnup calibration curve using the equilibrium core reactivity method of the RSG-GAS reactor. The reactivity value of each fuel element was measured at the same position within the reactor core to ensure that the measured burnup corresponds to the experimental core. The reactivity value of each fuel element was then extrapolated with the known burnup of the fuel element. The total control rod worth measurement was compared with Monte Carlo Serpent2 code calculations. The experimental fuel reactivity results were compared with the calculation results, showing a maximum discrepancy of -4.88%. Based on the reactivity measurement and calculation results, a fuel burnup calibration curve was successfully developed, which can be used to determine the burnup fraction of the RSG-GAS reactor.